Functional Outcome of Proximal Humerus Fracture Managed Surgically by Joshi’s External Stabilizing System - Kandel, Prakriti Raj; Shrestha, Bipan; Shrestha, Kishor Man; Shrestha, Shreshal; Chhetri, Pradip (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: The ideal management of proximal humerus fracture is still controversial despite various treatment options. Conservative treatment with slab is fraught with shoulder stiffness and malunion while surgical treatment with plates and nail is fraught with infection and blood loss. Therefore, Joshi External Stabilization System (JESS) being a minimally invasive percutaneous procedure can be the ideal treatment for these fractures. MATERIAL AND METHODS: This prospective and observational hospital based study was carried out in Orthopedics Department, Universal College of Medical Sciences Teaching Hospital (UCMS-TH) from December 2018 to January 2021. All patients with traumatic proximal humerus fracture who fulfilled the inclusion criteria were enrolled in the study and were treated with JESS. Fracture was classified according to Neer classification and functional outcome was assessed according to Constant Murley Score (CMS) system. Post-operatively patients were regularly followed at 6 weeks, 3 months and 6 months. RESULTS: There was statistically significant difference in VAS score (p<0.05) measured at six weeks, three months and six months; and CMS (p<0.05) at three months and six months. There was statistically significant difference between fracture type (Neer type) and fracture union (p<0.05). But the association between functional outcome and type of fracture was statically insignificant (p>0.05). CONCLUSION: Displaced proximal humerus fracture when treated surgically with JESS has good functional and radiological outcome. It produces less pain, less stiffness and greater Range of Motion (ROM).